THE STATUS QUO OF METAL TECHNOLOGY IN THE CENTRAL AND NORTHERN COAST OF PERU DURING THE LATE INTERMEDIATE PERIOD - Vetter Parodi, Luisa (2011)
Studies made on Pre-Colombian metallurgy technology from the Northern Coast have notably increased in recent years. Nevertheless, in the Central Coast the issue has not yet aroused the interest of researchers. The little knowledge gathered on metallurgy from this area reveals that development was not as advanced as in its northern pair, especially in the Late Intermediate Period, when northern cultures became users of all goldsmiths techniques, all metals and most alloys known at the time.